2009
DOI: 10.1038/hr.2009.29
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eplerenone, a selective mineralocorticoid receptor antagonist, on clinical and experimental salt-sensitive hypertension

Abstract: Mineralocorticoid receptors (MRs) are expressed in non-epithelial tissues, such as blood vessels, the heart and adipose tissue. The combined effects of aldosterone and insulin link the metabolic syndrome with hypertension and salt sensitivity. Eplerenone is the newly developed inhibitor of MRs that has significantly fewer adverse effects than similar doses of spironolactone. Eplerenone has been reported to have anti-hypertensive and protective effects on cardiovascular and renal injury in salt-sensitive hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 33 publications
1
13
1
Order By: Relevance
“…4,5 The beneficial effects of the MR antagonist spironolactone or the more specific antagonist eplerenone on end-organ damage have been studied in animal models. [6][7][8][9][10] It has been reported that MRs regulate epithelial Na channels (ENaCs) that are important for the regulation of sodium transport and the maintenance of extracellular fluid volume and arterial pressure (AP) in the kidney. 11 Recent studies have reported the distribution of MRs or ENaCs in the choroid plexus, ependyma and neurons, such as those in the supraoptic nucleus, paraventricular nucleus and nucleus tractus solitarius.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The beneficial effects of the MR antagonist spironolactone or the more specific antagonist eplerenone on end-organ damage have been studied in animal models. [6][7][8][9][10] It has been reported that MRs regulate epithelial Na channels (ENaCs) that are important for the regulation of sodium transport and the maintenance of extracellular fluid volume and arterial pressure (AP) in the kidney. 11 Recent studies have reported the distribution of MRs or ENaCs in the choroid plexus, ependyma and neurons, such as those in the supraoptic nucleus, paraventricular nucleus and nucleus tractus solitarius.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] In keeping with the pathophysiological roles, aldosteronism and oxidative stress are salutary responses to mineralocorticoid receptor antagonism. [12][13][14][15][16] AN EXPERIMENTAL MODEL OF ALDOSTERONISM Aldosterone/salt treatment We have worked extensively with the ALDOST model, wherein eightweek-old male Sprague-Dawley rats are first uninephrectomized to reduce renal mass available for Na + excretion. An osmotic minipump filled with ALDO is implanted subcutaneously; it releases ALDO (0.75 mg h Ă€1 ) to raise PAC to levels found in patients with congestive heart failure, whereas drinking water is fortified with 1% NaCl to create inappropriate aldosteronism and 0.4% KCl to prevent hypokalemia and associated cardiac pathology.…”
Section: Aldosteronism Defined and Stimuli That Regulate Adrenal Aldomentioning
confidence: 99%
“…This may explain why microinjection of eplerenone into the NTS reversed the baroreflex sensitivity induced by the high sodium load. Indeed, eplerenone exhibits a potential antihypertensive effect with a slightly different profile from that of spironolactone, and eplerenone is effective against salt-sensitive hypertension (15). It is also possible that a high sodium load may have altered the activity of HSD2, resulting in a change of the balance between aldosterone and corticosterone production.…”
mentioning
confidence: 99%